Kewenangan Kepala Otorita dalam Penyusunan Perencanaan Pembangunan Ibu Kota Negara Nusantara - Diani Sadiawati; Rianda Dirkareshza; Wicipto Setiadi; Elizabet Devi Permatasari (Jurnal Penelitian Hukum De Jure, 2023)
Preparing development plans for the National Capital City (IKN) of Nusantara is one of the authorities that must be carried out by the Government to ensure the continuity and progress of the State’s development in accordance with the mandate of Law Number 3 of 2022 concerning the National Capital City. However, in reality, the formulation of development plans for the new National Capital City still experiences problems related to the Nusantara Capital City Authority (OIKN). Problems with OIKN in preparing development plans for the new National Capital City can come from various factors, such as disharmony of laws and regulations. This study aimed to find out the power of the chairman of authority related to the planning and development of the Nusantara Capital City and the concept of the chairman of authority in preparing the Nusantara Capital City development plans in harmony with the Long-Term National Development Plan. The method used in this study was the Normative Method with interviews and Legislative, Conceptual, Philosophical, and Futuristic approaches which were analyzed in a descriptive-analytic manner and processed qualitatively. The results of the study show that in planning for the development of the national capital city, the chairman of authority has the power to determine the location of the new national capital city according to geographical, social, and economic conditions and to prepare a master plan. However, IKN development plans that are not guided by the Long-Term National Development Plan (RPJPN) as national development guidelines, but are instead guided by the Government’s Master Plan (RIP) will create their own problems. The recommendation from this research is to launch a Hybrid Government system followed by the process of integrating the RIP into the 2025-2045 RPJPN so that it becomes the country’s grand master plan for the next 20 years.